New Directions for Evaluation (Vol. 102) - Mary Keating (The Evaluation Center at Western Michigan University, 2004)
A summary of issue 102 of New Directions for Evaluation entitled "In Search of Cultural Competence in Evaluation - Toward Principles and Practices" published in summer 2004.